2021
DOI: 10.1155/2021/5510566
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study on the Gas Drainage Optimization Based on the Effective Borehole Spacing in Sima Coal Mine

Abstract: Based on the dynamic expressions of permeability and porosity of the coal seam derived in the paper, a multiphysical field coupling numerical model of gas migration under the interaction of stress field and seepage field was established. The gas drainage project #3 Coal Seam operated by Sima Coal Industry Co., Ltd., was selected as the study object. Taking different drainage time periods in various positions of drainage holes into consideration, combined with the advance situation of the 1207 working face in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…To better study the change in gas pressure in the borehole, a two-dimensional reference plane was intercepted on the cross-section YZ with X as the 30 m coordinate, and the yellow arrows in Figure 5 correspond to the transformation relationship between the two-dimensional cross-section and the three-dimensional model. The parameters used in the numerical simulation are mainly from field engineering measurements and refer to some quantitative research papers [31][32][33][34], as shown in Table 2.…”
Section: Numerical Model and Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…To better study the change in gas pressure in the borehole, a two-dimensional reference plane was intercepted on the cross-section YZ with X as the 30 m coordinate, and the yellow arrows in Figure 5 correspond to the transformation relationship between the two-dimensional cross-section and the three-dimensional model. The parameters used in the numerical simulation are mainly from field engineering measurements and refer to some quantitative research papers [31][32][33][34], as shown in Table 2.…”
Section: Numerical Model and Parametersmentioning
confidence: 99%
“…According to the "Basic Indicators of Gas Extraction in Coal Mines", the area where the gas pressure around the borehole is less than 0.74 MPa within a certain extraction time is the extraction standardized area [6,35,36]. It can be seen from Figure 6 measurements and refer to some quantitative research papers [31][32][33][34], as shown in Table 2…”
Section: Effective Radius Of Gas Extraction For Extraction Cyclementioning
confidence: 99%
“…Both adsorbed and free gas are present in the pore system of the coal matrix [33], and the gas content of the matrix system, mm, is as follows:…”
Section: Matrix Pore Gas Diffusion Equationmentioning
confidence: 99%
“…where ρ c is the pseudo-density of the coal body, kg/m 3 ; M c is the molar mass of methane, kg/mol; R is the gas constant, J/(mol•K); T is the temperature of the coal seam, K; and V M is the molar volume of the gas at standard conditions, L/mol. The equilibrium state of the coal bed matrix system and the fissure system is broken under the action of the pressure difference, and the diffusion of adsorbed gas in the matrix provides a mass source for the fissure gas transport due to the different velocities of matrix diffusion and fissure seepage [33], which can be obtained from the mass conservation theorem:…”
Section: Matrix Pore Gas Diffusion Equationmentioning
confidence: 99%
“…(1) Reasonable Borehole Spacing in a Fully Pressure-Relief Zone. To determine reasonable borehole spacing in the fully pressure-relief zone (see Figure 10), according to the literature [24], five cases of gas extraction with borehole spacing being 20 m, 25 m, 30 m, 35 m, and 40 m are simulated, respectively. The gas pressure-time curves for monitoring point under varying borehole spacings are given in Figure 20.…”
Section: Reasonable Borehole Spacing In Different Pressure Relief Zonesmentioning
confidence: 99%